2021
DOI: 10.29244/jhi.12.1.69-80
|View full text |Cite
|
Sign up to set email alerts
|

Pengaruh Suhu dan Waktu Pengeringan terhadap Karakteristik Fisikokimia Buah Naga Merah (Hylocereus polyrhizus (Weber) Britton & Rose) Kering

Abstract: Sebagai salah satu komoditas hortikultura, buah naga merah (Hylocereus polyrhizus (Weber) Britton & Rose) adalah komoditas yang mudah mengalami kerusakan setelah panen. Penelitian ini bertujuan untuk mengetahui pengaruh suhu dan waktu pengeringan terhadap karakteristik fisikokimia buah naga merah kering. Rancangan penelitian yang digunakan adalah rancangan acak lengkap dengan dua faktor perlakuan. Faktor pertama adalah suhu pengeringan terdiri atas tiga taraf, yaitu 40, 50 dan 60 °C dan faktor ke-dua adala… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 14 publications
1
0
0
Order By: Relevance
“…Based on these results, it can be concluded that the longer drying time led to a smaller yield. The results were in accordance with research conducted by Santi (2021) on dragon fruit, which stated that a longer drying time could produce a smaller yield of product (12-15%). Other research also reported that increasing drying time could decrease product yield.…”
Section: Yieldsupporting
confidence: 91%
“…Based on these results, it can be concluded that the longer drying time led to a smaller yield. The results were in accordance with research conducted by Santi (2021) on dragon fruit, which stated that a longer drying time could produce a smaller yield of product (12-15%). Other research also reported that increasing drying time could decrease product yield.…”
Section: Yieldsupporting
confidence: 91%